Ballistic limit velocity of tungsten alloy spherical fragment penetrating Ti/Al3Ti-laminated composite target plates. (27th April 2020) - Liu, Yingbin; Yin, Chufan; Hu, Xiaoyan; Yuan, Meini
To determine the ballistic limit velocity of titanium–titanium tri-aluminide (Ti/Al3 Ti)-laminated composites under the action of tungsten alloy spherical fragments, a type of 12.7 mm ballistic gun loading system was used to test the tungsten alloy spherical fragments vertically impacting the Ti/Al3 Ti-laminated composite targets with different thickness. The relationship between the ballistic limit velocity and the target area density of the Ti/Al3 Ti-laminated composite was obtained. As the area density increased, the ballistic limit velocity and the ballistic energy absorbed by the target plate also enhanced. Based on the dimensional analysis and similarity theory, a simulation law of tungsten alloy spherical fragments penetrating Ti/Al3 Ti-laminated composite targets with different thickness was studied and an empirical formula for the ballistic limit velocity was obtained. The research results had an important application value for the optimal design of the light armor protection structure.